Designing Learning Trajectory on Data Distribution Measurement through PMRI - Nursyahidah, Farida; Albab, Irkham Ulil; Rubowo, Maya Rini (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
The concept of data distribution measures plays a pivotal role in statistical education, fostering students’ data literacy, critical thinking, and evidence-based decision-making. Despite its importance, many students continue to struggle with interpreting statistical data, demonstrating low levels of statistical reasoning and limited ability to apply these concepts to real-world contexts. Addressing this gap, this study introduces a culturally grounded and context-based instructional design that integrates the traditional Javanese calendar system, Pranata Mangsa, into the learning of data distribution measures. The objective of this research is to develop a learning trajectory that supports students’ conceptual understanding of data distribution through meaningful and realistic mathematical experiences. This study involved 32 eighth-grade students from a junior high school in Central Java and employed a design research methodology encompassing three phases: preparation for the experiment, experimental design, and retrospective analysis. The instructional activities were implemented using the Video-assisted Pendidikan Matematika Realistik Indonesia (PMRI) approach. The resulting learning trajectory comprises three interconnected activities, namely analyzing Pranata Mangsa video content to gather and present data, deriving formulas for data distribution measures, and solving contextual problems linked to the cultural theme. The findings indicate that the integration of culturally relevant contexts and visual media in PMRI effectively enhances students’ comprehension of statistical concepts. This research contributes to the field by offering a novel approach that bridges ethnomathematical elements with formal statistical instruction and serves as a reference for future studies seeking to incorporate local wisdom into mathematics education.